CONCEPT «AGRESSOR» IN ENGLISH POLITICAL DISCOURSE: LINGUISTIC INSIGHT - Gudkova, S.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Linguists engagement in discourse allows to explore the nature of speech from different points of view. The reason for this can be attributed to the increased attention to the human being and his inner potential from humanitarian research. Modern science in general and various linguistic sciences are defining new approaches to language research. One such new approach to language learning has been discursive analysis in an English-speaking political environment. The issue of speech aggression and the "aggressor" concept is considered to be interesting and relevant for philologists and linguists in the psycholinguistics, linguopragmatics and other related scientific directions. Nowadays it still remains interesting from both theoretical and practical points of view due to its interaction both with the humanities and language sciences, while also dealing with political, cultural and philosophical issues. The object of the study is political discourse. The subject is the study of implicit components of meaning on which semantics is based and how the concept « Aggressor» is represented in conflict political discourse. The choice of the research topic is justified by a number of reasons, the main of which are considered to be the tension of relations in the sphere of international political communication. The research is based on controversial texts of speeches by American politicians, press conferences, articles, etc. According to the study the main linguistic means for representing the considered concept " agressor" the modal-evaluating evolutives of prohibition, illegality various stylistic methods are known as being the most widely used.